Tinjauan Pengelolaan Sampah dalam Perspektif Peraturan Daerah Kabupaten Indramayu Nomor 12 Tahun 2016 dan Hukum Islam di Ma’had Al-Zaytun - Anida Atulloh Hanifa; Siti Ngainnur Rohmah; Taufiqurachman Taufiqurachman (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Waste management is a significant issue in Indonesia, including in Indramayu Regency, with the volume of waste increasing annually, necessitating proper handling to mitigate its negative impact on health. This study focuses on waste management at Ma'had Al-Zaytun from the perspectives of Regional Regulation No. 12 of 2016 of Indramayu Regency and Islamic law. A qualitative research method was employed, utilizing observation, interviews, and document analysis, with qualitative data analysis techniques. The findings indicate that waste management at Ma'had Al-Zaytun aligns with Article 15 of the Regional Regulation by implementing waste reduction through limiting plastic use and recycling, and waste handling through sorting, collecting, transporting, and processing food waste. However, the use of open dumping and incineration methods requires further evaluation to enhance effectiveness and minimize negative impacts. From the perspective of Islamic law, waste management at Ma'had Al-Zaytun complies with the principles of Fiqh Al-Biah, which emphasize environmental preservation, pollution prevention, reducing excessive consumption through recycling, and reforestation through tree planting—reflecting a commitment to creating an eco-friendly Islamic educational environment.